Book History without Old Books. Issue 2 (1st October 2021) - Levy, Michelle; Moffatt, Kate
Abstract : During the pandemic, the closure of university libraries and Special Collections meant that there were few opportunities for students to interact with the print and manuscript material of the Romantic period. These conditions created an entirely new set of interactions between instructors and students, students and their classmates, and students and their objects of study. To address these new conditions, we created a series of assignments that sought to recreate a sense of the opportunities and pleasures of the sensory experience in an archive; to foster an understanding of both the material history of Romantic literary culture and of material culture more broadly; and finally to connect students emotionally with the objects of their study. This essay reports on the outcomes of these assignments and what they can teach us about attempts to integrate play, discovery, and interactivity with material objects into the study of Romantic writing.